Uncovering genetic contributors to developmental delay and intellectual disability: a focus on CNVs in pediatric patients - Yilun Tao; Yilun Tao; Hongzhi Guo; Dong Han; Miao Yang; Ting Lun; Lihong Wang; Wenxia Song; Haiwei Wang; Xiaoze Li (Frontiers in Genetics)
BackgroundDevelopmental delay (DD) and intellectual disability (ID) are prevalent in children and often have genetic causes, particularly copy number variations (CNVs). Chromosomal microarray analysis (CMA) and whole-exome sequencing (WES) are key diagnostic tools for identifying genetic contributions to these disorders. This study assesses the prevalence and clinical impact of CNVs in pediatric DD and ID patients.MethodsNinety-nine pediatric patients with DD or ID underwent CMA or WES. Of these, 82 received SNP array analysis, while 17 had WES. CNV pathogenicity was assessed using established databases and ACMG guidelines, with inheritance patterns determined where possible.ResultsAcross the 99 patients, 43 CNVs were identified in 40 individuals, with 32 classified as clinically significant, resulting in a diagnostic rate of 30.3%. These findings included 24 deletions (75%), 7 duplications (22%), and 1 instance of loss of heterozygosity (3%). Of the CNVs with known inheritance, 65.2% were de novo. Recurrent CNVs made up 36.4% of the total, especially in regions 15q11.2-q13.1, 16p11.2, and 22q11.2. Additionally, 11 CNVs were categorized as variants of uncertain significance (VOUS).ConclusionThis study supports CMA as an effective diagnostic tool for DD and ID, highlighting the importance of family-based CNV testing for genetic counseling. The findings emphasize the need for comprehensive genetic testing to improve diagnostic accuracy, with future multi-omics approaches potentially clarifying VOUS mechanisms and CNV variability in neurodevelopmental disorders.